Pemberian Formula Daun Sirih Cina dan Jahe Merah terhadap Kadar LDL dan Trigliserida pada Tikus Obesitas - Bintanah, Sufiati; Saraswati, Retno Arra; Al Sa’diyah, Imtiyaz Halimah; Ayuningtyas, Rr. Annisa (Program Studi Gizi, Universitas Bumigora, 2025)
Obesity is a condition characterized by excessive fat accumulation and is associated with elevated levels of low-density lipoprotein (LDL) cholesterol and triglycerides in the blood. A combination of herbal ingredients such as Chinese betel leaf (Peperomia pellucida L.) and red ginger (Zingiber officinale var. rubrum) is known to contain flavonoids and gingerol, which play a role in reducing blood lipid levels. This study aimed to evaluate the effect of a formulation of Chinese betel leaf and and red ginger on LDL and triglyceride levels in obese male Sprague Dawley rats.. This study was conducted using a true experimental design with a pretest-posttest control group approach. A total of 30 rats were divided into five treatment groups, including a control group and three intervention groups (P1: Chinese betel leaf, P2: red ginger, and P3: a combination of both). The results showed that the combination of 88 mg Chinese betel leaf and 115.5 mg red ginger significantly reduced LDL levels by 57.94% and triglyceride levels by 41.09% (p < 0.05). Conclusion is the combination of Chinese betel leaf and red ginger simplicia was effective in lowering blood lipid levels in an obese rat model.